Flow Giese reaction using cyanoborohydride as a radical mediator - Fukuyama, Takahide; Kawamoto, Takuji; Kobayashi, Mikako; Ryu, Ilhyong (Beilstein Journal of Organic Chemistry, 2013)
Tin-free Giese reactions, employing primary, secondary, and tertiary alkyl iodides as radical precursors, ethyl acrylate as a radical trap, and sodium cyanoborohydride as a radical mediator, were examined in a continuous flow system. With the use of an automated flow microreactor, flow reaction conditions for the Giese reaction were quickly optimized, and it was found that a reaction temperature of 70 °C in combination with a residence time of 10–15 minutes gave good yields of the desired addition products.
Keywords: continuous flow system; cyanoborohydride; flow chemistry; iodoalkanes; microreactor; tin-free Giese reaction

Radicals in Organic Synthesis - Renaud, P.; Sibi, M. P. (Wiley-VCH, 2001)

Advanced Free Radical Reactions for Organic Synthesis - Togo, H. (Elsevier, 2004)

Radicals in Synthesis III - Heinrich, M. R.; Gansäuer, A. (Springer, 2012)

Encyclopedia of Radicals in Chemistry, Biology and Materials - Chatgilialoglu, C.; Studer, A. (Wiley, 2012)

(untitled) - Rowlands, G. J. (Tetrahedron, 2009)

(untitled) - Giese, B. (Angew. Chem., Int. Ed., 1983)

(untitled) - Fisher, H.; Radom, L. (Angew. Chem., Int. Ed., 2001)

(untitled) - Giese, B.; González-Gómez, J. A.; Witzel, T. (Angew. Chem., Int. Ed., 1984)

(untitled) - Gerth, D. B.; Giese, B. (J. Org. Chem., 1986)

(untitled) - Ryu, I.; Uehara, S.; Hirao, H.; Fukuyama, T. (Org. Lett., 2008)

(untitled) - Kobayashi, S.; Kawamoto, T.; Uehara, S.; Fukuyama, T.; Ryu, I. (Org. Lett., 2010)

(untitled) - Kawamoto, T.; Fukuyama, T.; Ryu, I. (J. Am. Chem. Soc., 2012)

(untitled) - Kawamoto, T.; Ryu, I. (Chimia, 2012)

(untitled) - Curran, D. P.; Solovyev, A.; Makhlouf Brahmi, M.; Fensterbank, L.; Malacria, M.; Lacote, E. (Angew. Chem., Int. Ed., 2011)

(untitled) - Ueng, S.-H.; Fensterbank, L.; Lacôte, E.; Malacria, M.; Curran, D. P. (Org. Lett., 2010)

(untitled) - Ueng, S.-H.; Fensterbank, L.; Lacôte, E.; Malacria, M.; Curran, D. P. (Org. Biomol. Chem., 2011)

(untitled) - Pan, X.; Lacôte, E.; Lalevée, J.; Curran, D. P. (J. Am. Chem. Soc., 2012)

(untitled) - Kawamoto, T.; Okada, T.; Curran, D. P.; Ryu, I. (Org. Lett., 2013)

Micro Process Engineering - Hessel, V.; Renken, A.; Schouten, J. C.; Yoshida, J. (Wiley-VCH, 2009)

Microreactors in Organic Synthesis and Catalysis - Wirth, T. (Wiley-VCH, 2013)

(untitled) - Jas, G.; Kirschning, A. (Chem.–Eur. J., 2003)

(untitled) - Fukuyama, T.; Rahman, M. T.; Sato, M.; Ryu, I. (Synlett, 2008)

(untitled) - Yoshida, J.; Saito, K.; Nokami, T.; Nagaki, A. (Synlett, 2011)

(untitled) - Sugimoto, A.; Sumino, Y.; Takagi, M.; Fukuyama, T.; Ryu, I. (Tetrahedron Lett., 2006)

(untitled) - Sugimoto, A.; Fukuyama, T.; Sumino, Y.; Takagi, M.; Ryu, I. (Tetrahedron, 2009)

(untitled) - Matsubara, H.; Hino, Y.; Tokizane, M.; Ryu, I. (Chem. Eng. J., 2011)

(untitled) - Fukuyama, T.; Kobayashi, M.; Rahman, M. T.; Kamata, N.; Ryu, I. (Org. Lett., 2008)

(untitled) - Wienhöfer, I. C.; Studer, A.; Rahman, M. T.; Fukuyama, T.; Ryu, I. (Org. Lett., 2009)

(untitled) - Fukuyama, T.; Rahman, M. T.; Kamata, N.; Ryu, I. (Beilstein J. Org. Chem., 2009)

(untitled) - Fukuyama, T.; Kajihara, Y.; Ryu, I.; Studer, A. (Synthesis, 2012)

Encyclopedia of Radicals in Chemistry, Biology and Materials - Fukuyama, T.; Ryu, I. (Radical Chemistry by Using Flow Microreactor Technology, 2012)

(untitled) - Sugimoto, A.; Fukuyama, T.; Rahman, M. T.; Ryu, I. (Tetrahedron Lett., 2009)